Extensive Genetic Diversity within the Dutch Clinical Cryptococcus neoformans Population - Hagen, Ferry (American Society for Microbiology, 2012)
A set of 300 Dutch Cryptococcus neoformans isolates, obtained from 237 patients during 1977 to 2007, was investigated by determining the mating type, serotype, and AFLP and microsatellite genotype and susceptibility to seven antifungal compounds. Almost half of the studied cases were from HIV-infected patients, followed by a patient group of individuals with other underlying diseases and immunocompetent individuals. The majority of the isolates were mating type α and serotype A, followed by αD isolates and other minor categories. The most frequently observed genotype was AFLP1, distantly followed by AFLP2 and AFLP3. Microsatellite typing revealed a high genetic diversity among serotype A isolates but a lower diversity within the serotype D set of isolates. One patient was infected by multiple AFLP genotypes. Fluconazole and flucytosine had the highest geometric mean MICs of 2.9 and 3.5 μg/ml, respectively, while amphotericin B (0.24 μg/ml), itraconazole (0.08 μg/ml), voriconazole (0.07 μg/ml), posaconazole (0.06 μg/ml), and isavuconazole (0.03 μg/ml) had much lower geometric mean MICs. One isolate had a high flucytosine MIC (>64 μg/ml), while decreased susceptibility (≥16 μg/ml) for flucytosine and fluconazole was found in 9 and 10 C. neoformans isolates, respectively.